Does the shadow economy increase income inequality in the short- and long-run? Empirical evidence from Uganda - Stephen Esaku (Cogent Economics & Finance, 2021)
This paper investigates whether the size of the shadow economy increases income inequality in Uganda. This paper applies the autoregressive distributed lag (ARDL) bounds testing approach to cointegration, to test the long- and short-run relationship between the shadow economy and income inequality. The results indicate a positive and statistically significant relationship between the size of the shadow economy and income inequality in both the long-run and short-run, all else equal. The results show that a large size of the shadow economy significantly increases income inequality, in both the long- and short-run. This suggests that people who fail to be absorbed into the formal economy face fewer livelihood opportunities, giving them the incentive to operate in the shadow economy as a means of survival, for them and their families since there are fewer chances of success in the formal economy. Our findings suggest that income inequality could be partially driven by increasing informality in the country. The practical implication of these results is that policies aimed at tackling income inequality should also be directed at addressing the underlying factors that drive the shadow economy.
Keywords: D31; E25; E26; E62; N30; 330; gini coefficient; government spending; income distribution; income inequality; informal economy; shadow economy